PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN TEMUAN AUDIT BPK TERHADAP KINERJA PEMERINTAH - Reginald Gogo Acacius Dao; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2025)
This study aims to empirically examine the effect of local government characteristics and audit findings from the Audit Board of the Republic of Indonesia (BPK) on the performance of provincial governments in Indonesia. The characteristics analyzed include government size (total assets), regional wealth (ratio of Own-Source Revenue to total revenue), fiscal dependency on the central government (ratio of General Allocation Fund to revenue), and capital expenditure. The study is motivated by the importance of public accountability and the use of Regional Government Administration Reports (LPPD) and Regional Government Performance Evaluation (EKPPD) as official performance assessment instruments from the Ministry of Home Affairs.This research employs a quantitative approach using ordinal logistic regression analysis. The population consists of 34 provincial governments in Indonesia, selected using purposive sampling based on data completeness for the year 2022. Data were collected from official sources including the Ministry of Home Affairs, the Audit Board (BPK), and the Directorate General of Fiscal Balance. The dependent variable is the provincial government performance score, while the independent variables include government size, regional wealth, fiscal dependency, capital expenditure, and audit findings.The results indicate that government size has a positive and significant effect on performance, while audit findings have a significant negative effect. However, regional wealth, fiscal dependency, and capital expenditure do not show a significant effect. These findings support agency theory, which emphasizes the role of external monitoring and transparency in reducing information asymmetry. The study is expected to serve as a reference for local governments and oversight institutions in formulating more accountable financial management and governance policies.